The Global Economic Barometers: Composite indicators for the world economy - Klaus Abberger; Michael Graff; Aloisio Campelo; Anna Carolina Lemos Gouveia; Oliver Müller; Jan-Egbert Sturm (ETH Zurich, KOF Swiss Economic Institute, 2020)
This paper presents a coincident and a leading composite monthly indicator for the world business cycle - the Global Economic Barometers. Both target the world's output growth rate cycle. The calculation of these indicators comprises two main stages. The first consists of a variable selection procedure, in which a pre-set correlation threshold and the targeted leads to a reference series are used as selection criteria. In the second stage, the selected variables are combined and transformed into the respective composite indicators, computed as the first partial least squares factor with the reference series as response variable. In the last vintage referred to in this paper (December 2018), out of 6605 transformations from 1681 variables tested in the first stage, 1275 are selected to enter into the coincident and 1228 into the leading composite indicator. We analyse the characteristics of the two new indicators in a pseudo real-time setting and demonstrate that both are useful additions to the small number of indicators for the global business cycle published so far.
hdl:20.500.11850/401651
Keywords: E32; E37; 330; Business cycles; growth rate cycles; composite indicators; leading indicators; coincidentindicators; partial least squares; real-time simulations